Chapter 5.22 The Profession of Research Management and Administration in Czechia - Jaroslav Sip (Emerald Publishing Limited, 2023)
The chapter describes the emergence of the profession in Czechia. The major driver for universities and research and technology organisations (RTOs) was the country's accession to the European Union (EU) in 2004. The country has a rich system of national research, development, and innovation (R&D&I) funding and EU Framework Programmes are witnessing a slowly growing interest and success of Czech researchers. Yet, the major force in changing the research management and administration (RMA) culture and addressing the need of professionalising the environment of research administration, management, intellectual property rights, and technology transfer (TT) was European Structural and Investment Funds (ESIF). The Czech government repeatedly, through four EU programming periods, stressed the need for investments to reshape the research infrastructure, environment, and conditions on a scale not experienced by the universities or the RTOs ever before. The availability of EU funds and increasing emphasis on international cooperation enabled Czechia to witness slow, yet steady growth of demand to deliver better service in the field of RMA. This is illustrated through several EU-funded projects focussed on RMA skills development and the recent establishment of the Czech Association of Research Managers and Administrators (CZARMA) in 2022 (Masaryk University, 2022a).
10.1108/978-1-80382-701-820231056; 10.1108/978-1-80382-701-820231056; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262